EFEKTIFITAS PROMOSI DALAM PENINGKATAN PENJUALAN PRODUK KOSMETIK DI KOTA BLITAR - Denok Wahyudi Setyo Rahayu (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
Marketing is very important at product sales. Promotions support sales. Advertising is promotional activities. Purpose research is effectiveness of promotion as advertising to increasing sales product of cosmetics in Blitar city. The method is observation and direct interview with respondent by accidental sampling. The result is effective promotion in influencing consumer to buying it, so increase sale of cosmetics in the Blitar city.